Spanish societies' tax law and the fiscal adjustments to the accounting expense - Aldeia, Susana (2020)
This paper aims to understand why accounting expenses are not directly accepted as fiscal cost and how operates the fiscal adjustments, in the determination of the taxable base in the Corporate Income Tax (CIT) law. For this purpose, it analyses the legal acts and doctrine, in particular, it researches data sources of Spain: the Ley del Impuesto sobre Sociedades (LIS), it means, the Spanish Corporate Income Tax Law and, in particular, the Spanish doctrinal understandings. The results show that the tax law assumes the net profit measured under the General Accounting Principles, as a starting point for the tax base determination. This fact avoids the duplicate record of economic transaction in the companies, in both domains, fiscal and accounting. Nevertheless, the two dimensions have different objects, so net income may not be integrally considered for tax purposes; legislator makes the taxpayer make the fiscal adjustment to take the taxable income. It is supposed to have extraordinary tax corrections, but Spanish legislator presents a tax code with many exceptions, imposing an increasingly complex Spanish tax system.